Transmigrasi Era Otonomi Khusus di Provinsi Papua - La Pona (Humaniora, 2009)
Transmigration program was stopped in Papua in 2001. Some societis have consider that this program has failed to improve the local people life, prosperity, and tend to make social, cultural and political problems. Debating about the continuity of this program is still going on until now, even though, this program is still sustainable based on the ordinance of special autonomy in Papua Province. In the period of special autonomy, the implementation of transmigration program has been based on regulation territory of Papua province, and depends on the contribution of social and cultural scientists, because some of the most crucial problems of this program are social integration, social interaction, and social networking problems which have become barriers for diffusion and adoption of agricultural inovation process to indigenous people. The social and cultural planning in the past did not develop social networking to support the diffusion and innovation adoption process. This is the challenge for social and cultural scientists in this state to produce the new social and cultural approach, strategy, policy, program, and action. This contribution is very important in the interest of the state.